2012
DOI: 10.1093/aobpla/pls009
|View full text |Cite
|
Sign up to set email alerts
|

Modelling leaf photosynthetic and transpiration temperature-dependent responses in Vitis vinifera cv. Semillon grapevines growing in hot, irrigated vineyard conditions

Abstract: Grapevines growing in Australia suffer from high temperatures which have major effects on photosynthesis and transpiration. To learn more, gas exchange was measured over several seasons and then modelled across temperatures from 20 to 45°C and validated with independent data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 72 publications
1
17
0
3
Order By: Relevance
“…Stomatal opening and decrease in stomatal resistance, which implies the reciprocal of stomatal conductance, were observed under high temperatures, allowing the plants to avoid heat stress (Homma et al, 1999;Reynolds-Henne et al, 2010). In contrast, increasing temperature did not have a significant impact on stomatal conductance (Greer, 2012;Li et al, 2012). Seversike et al (2013) showed that the slope of transpiration response to VPD, which somewhat corresponded to canopy conductance, decreased when the VPD increased above 1.9 kPa at 25℃ at the whole plant level in soybean.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Stomatal opening and decrease in stomatal resistance, which implies the reciprocal of stomatal conductance, were observed under high temperatures, allowing the plants to avoid heat stress (Homma et al, 1999;Reynolds-Henne et al, 2010). In contrast, increasing temperature did not have a significant impact on stomatal conductance (Greer, 2012;Li et al, 2012). Seversike et al (2013) showed that the slope of transpiration response to VPD, which somewhat corresponded to canopy conductance, decreased when the VPD increased above 1.9 kPa at 25℃ at the whole plant level in soybean.…”
Section: Discussionmentioning
confidence: 90%
“…This is because increasing temperature simultaneously increases VPD, making it difficult to differentiate between the effects of high temperature and those of VPD (Weber et al, 1985;Greer, 2012;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Those figures show that the correlation of both stomatal conductance and transpiration rate that has a close relationship with photosynthetic rate with successively r 2 values are 0.89 and 0.88 was obtained; it indicates that at photosynthetic rate was seemingly controlled by stomatal conductance and transpiration rate. Therefore it can be said clearly also, that all changes in photosynthesis were highly correlated with transpiration and stomatal conductance [17]. Furthermore, it is explained in Stomatal conductance of CO 2 before watering in the week eighth, the interaction between varieties with water supply significantly (p < 0,001) where a stomatal conductance will decrease due to lack of water and there is a signifficant effect in each watered as well as varieties.…”
Section: Volumetric Water Content (Vwc)mentioning
confidence: 86%
“…Some commercially irrigated plants, such as grape vines, can double their transpiration rates as ambient temperatures increase from 20 o C to 40 o C and can thus lower their leaf temperatures by several Centigrade degrees (see, for example, Greer 2012). The extent to which mature eucalypts can do this under irrigation regimes that are probably less than those used for commercial agricultural production is not known.…”
Section: Discussionmentioning
confidence: 99%